2019
DOI: 10.1155/2019/2417418
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 (Shenyi Capsule) Combined with Chemotherapy for Digestive System Cancer in China: A Meta-Analysis and Systematic Review

Abstract: Objective. In China, ginsenoside Rg3 is often used in combination with chemotherapy to treat digestive system cancer. We here performed a meta-analysis and systematic review to provide a much needed high-quality evaluation of the efficacy and safety of ginsenoside Rg3 combined with chemotherapy in these cancers. Materials and Methods. The PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, and Weipu (VIP) databases were searched. All randomized controlled trials (RCTs) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The susceptibility of HOS cells to Rg5 was slightly weaker than that of MG-63 and U2OS cells. Cell apoptosis was closely related to cell proliferation inhibition [ 29 , 30 ]. FACS experiment revealed that Rg5 significantly induced human osteosarcoma cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of HOS cells to Rg5 was slightly weaker than that of MG-63 and U2OS cells. Cell apoptosis was closely related to cell proliferation inhibition [ 29 , 30 ]. FACS experiment revealed that Rg5 significantly induced human osteosarcoma cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ginsenoside Rg3 can decrease the expression of vascular endothelial growth factor (VEGF), and its antitumor effects may be mediated through suppression of ERK and Akt signaling (Meng et al, 2019). Our prior work indicated that ginsenoside Rg3 combined with chemotherapy can improve the clinical efficacy (objective response rate, disease control rate, survival rate, Karnofsky Performance Scale) and alleviate treatment-induced side effects (gastrointestinal dysfunction, the decline of leucocyte count) for digestive system cancer (Pan et al, 2019). The previous research only suggested that ginsenoside Rg3 can improve the reduction of leucocyte counts in patients with digestive system cancer, but for the chemotherapy-induced decrease in hemoglobin, platelet, and neutrophil counts is unclear.…”
Section: Summary Of Reported Evidencementioning
confidence: 99%
“…At present, the clinical management of cancer always involves several conventional modalities, including surgical resection, radiotherapy, immunotherapy, biotherapy, and chemotherapy [ 2 ]. Chemotherapy is currently the most commonly used treatment for cancer [ 3 ]. Given that it is difficult to determine an appropriate dosage of conventional chemotherapeutic agents, side effects, such as a reduction in bone density and immunosuppression, often result from high doses, while low levels may not produce desired effects [ 2 ].…”
Section: Introductionmentioning
confidence: 99%